2017
DOI: 10.1155/2017/7209303
|View full text |Cite
|
Sign up to set email alerts
|

Fix‐and‐Optimize and Variable Neighborhood Search Approaches for Stochastic Multi‐Item Capacitated Lot‐Sizing Problems

Abstract: We discuss stochastic multi-item capacitated lot-sizing problems with and without setup carryovers (also known as link lot size), S-MICLSP and S-MICLSP-L. The two models are motivated from a real-world steel enterprise. To overcome the nonlinearity of the models, a piecewise linear approximation method is proposed. We develop a new fix-and-optimize (FO) approach to solve the approximated models. Compared with the existing FO approach(es), our FO is based on the concept of " -degreeconnection" for decomposing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As mentioned before, the underlying constraints to consider vary significantly from one industry to another. Recent papers dealing with simultaneous lot sizing and scheduling (LSS) problems put more focus on particular features of these industries [7]: the beverage industry [10], [11] and [12], steel manufacturing [13], [14] and [15], the automotive industry [16] and [17], glass-container manufacturing [18], the tile industry [19], the chemical industry [20], and the paper industry [21]. Additionally some research has been conducted in the tire industry [22] and [23] and more specifically in the off-the-road tire industry [24] and [25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before, the underlying constraints to consider vary significantly from one industry to another. Recent papers dealing with simultaneous lot sizing and scheduling (LSS) problems put more focus on particular features of these industries [7]: the beverage industry [10], [11] and [12], steel manufacturing [13], [14] and [15], the automotive industry [16] and [17], glass-container manufacturing [18], the tile industry [19], the chemical industry [20], and the paper industry [21]. Additionally some research has been conducted in the tire industry [22] and [23] and more specifically in the off-the-road tire industry [24] and [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Toscano et al [36] have recently developed a F&O algorithm to solve a synchronized two-stage CLSP with mandatory temporal cleaning and sequence-dependent changeover in a soft drink company. F&O heuristics have also been combined with local search such variable neighborhood search as in [37] and [13]. Li et al [13] dealt with a multi-item lot sizing problem in the steel industry with demand class formulation and stochastic demand where backlogging and overtime costs were also incurred.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that this formulation has a very tight linear relaxation that provides a far superior computational performance as compared to traditional period based formulations present in the literature. It should also be remarked that there are number of recent studies addressing the stochastic multi-item CLSP with setup carryovers ( [25]), energy concerns ( [26]), and rolling horizon framework under service level constraints ( [27], [28]).…”
Section: *Corresponding Authormentioning
confidence: 99%
“…poses the original problem by fixing values of binary variables based on their interrelatedness. That approach has also been integrated into a variable neighborhood search framework, achieving excellent results for lot sizing (Chen, 2015;Li et al, 2017) and transportation (Toschi et al, 2018) problems. introduced a hybrid metaheuristic called Construct, Merge, Solve & Adapt (CMSA).…”
Section: Introductionmentioning
confidence: 99%